Recent developments of carbon-based electrocatalysts for hydrogen evolution reaction. (October 2016) - Zhou, Weijia; Jia, Jin; Lu, Jia; Yang, Linjing; Hou, Dongman; Li, Guoqiang; Chen, Shaowei
Abstract: Development of effective technologies for clean and sustainable hydrogen energy has been attracting great attention. Toward this end, an effective and promising approach is based on the electrolysis of water for hydrogen production. To date, the most effective hydrogen evolution reaction (HER) electrocatalysts are Pt-group metals with a low overpotential to generate large cathodic current densities. However, the high cost and scarcity severely limit their broad utilization. As alternatives to Pt electrocatalysts, transition metal compounds as effective HER catalysts have been prepared in a series of recent studies. However, thus far, it remained a great challenge to develop highly active HER catalysts with a low overpotential based on earth-abundant and cost-effective materials. Recently, the new significant developments about carbon-based electrocatalysts with a low overpotential toward HER have stimulated a great deal of the researchers' interest. In particular, the catalytic activity of carbon based-catalysts can be enhanced by transition metal nanoparticles as core and nonmetal doping into carbon skeleton, which can modulate the electronic state density of carbon to produce new active sites for HER. In this feature article, we review the research progress in the development of carbon-based electrocatalysts toward HER in acid electrolytes throughout the past few years. In addition, some notable matters and challenge in the research of HER are discussed in this review. Graphical abstract: Highlights: Heteroatoms including N, S, P and B improve HER catalytic activity of carbon. Metals as core modulate the electronic state density of carbon shell to produce new active sites. Some challenges for carbon based electrocatalysts are discussed.